The effect of stirrup length on impact attenuation and its association with muscle strength - Keener, M. M.; Critchley, M. L.; Layer, J. S.; Johnson, E. C.; Barrett, S. F.; Dai, B. (The Journal of Strength and Conditioning Research, 2021)
Horseback-riders have a high prevalence of low back injuries, which may be related to the repetitive low back impacts experienced in riding. The purposes of this study were to quantify the effect of 3 stirrup lengths and 2 riding styles on the peak acceleration experienced by the rider and the association between the peak acceleration and the rider's different elements of muscle strength. Thirteen female riders performed a sitting or rising trot at each of the 3 stirrup lengths (2-point length, mid-seat length, or dressage length), while the acceleration of the tibia, sacrum, seventh cervical vertebra (C7), and head were collected. Subjects completed a push-up, a vertical jump, and 4 core exercises to assess upper-body strength, lower-body strength, and core endurance, respectively. Peak acceleration of the sacrum, C7, and head were generally lower in the standing phase of the rising trot compared with the sitting phase of either the sitting or rising trot, particularly at the shortest stirrup length. Peak acceleration of the sacrum, C7, and head decreased as the stirrup length was shortened in the standing phase of the rising trot. Canonical correlations showed nonsignificant correlations between strength measurements and peak acceleration. Riding with more weight supported through the legs with a short stirrup length may decrease low back impacts and their associated injury risk. Technique training is likely needed to encourage riders to use lower-body and core strength for impact attenuation.